Inventory management using the abc classification method in the warehouse of tectum, peru - Auqui Aguirre, Odeht Geraldine Kaory (2025)
Inventory management has a valuable role because it identifies the loss of raw materials and maintains the economic sustainability of companies in the market. This research aims to measure inventory control and provide analysis through appropriate methodologies, such as the ABC classification system and the weighted moving average, improving warehouse management and the sales level of the company Tectum. For this purpose, the preliminary diagnosis was made employing a survey, considering The permanence at work, economic situation, classification of products according to importance, frequency of registration of inputs and outputs, knowledge of inventory management and control, and its application; which gave as a primary result that, despite not knowing the storage of products thoroughly, if they know their benefits, so they keep a record where they are classifying the products by importance. For the ABC classification analysis, 30 products derived from Aluzinc were used, of which 13 belong to group A, the most essential product, the pre - painted Aluzinc Red RAL 3020 (0.30mm). In addition, it is known which products have higher rotation, considering the relevance in obtaining profits in the company, and that some products could be eliminated due to the lack of circulation. Therefore, with the ABC classification system and the weighted moving average, it is ensured that the available products are delivered on time to meet the demand and avoid production delays.